The Effect of Sustainability Report Disclosure and Company Size on Company Value with Profitability as a Moderation Variable - Pakiding, Daniel L; Kampo, Kunradus; Sucianto, Michael Dufan (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2024)
Purpose – The purpose of this study is to examine the role of profitability moderation on the effect of sustainability report disclosures and firm size on firm value. Design/methodology/approach – The research method uses moderated regression analysis to analyse profitability effect on the relation between the dependent and independent variables. Findings – The results of this study indicate that sustainability reports have a positive and significant effect on firm value. Firm size have a negative and insignificant influence on firm value and profitability moderates the effect of sustainability report disclosures and firm size on firm value. Originality – Company samples are manufacture companies listed on the Indonesia Stock Exchange for the period of 2017-2019 that disclose financial reports and sustainability reports in a row, so that the total sample obtained in the 3-year period Keywords: Sustainability Report, Firm Size, Firm Value, Profitability, Stakeholder Theory, Legitimacy Theory Paper Type Research Result